2017
DOI: 10.4209/aaqr.2016.02.0054
|View full text |Cite
|
Sign up to set email alerts
|

Absorbing Aerosols, Possible Implication to Crop Yield - A Comparison between IGB Stations

Abstract: The current study compares black carbon radiative effects at the densely populated plain station, Varanasi and the lesser populated plateau station Ranchi with large forest cover but with numerous open coal mines. While the measured average black carbon mass density (BC) reduces from February to March at Ranchi following an increase in convective mixing, it is observed to increase by 150% from February to March in Varanasi, as transport from northeast forest fires increases. It is observed that absorption due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…A statistical model of historical rice harvest in India, coupled with a regional climate scenario, indicated that there has been a slowdown in the increase in production over the last two decades due to increased brown cloud and greenhouse gas [30]. Similarly, Latha et al [31] compared the radiative forcing of atmospheric black carbon at two locations in IGP, Varanasi and Ranchi by using Santa Barbara DISTORT Atmospheric Radiative Transfer (SBDART) model and concluded that the incoming radiation is reduced by about 5% due to black carbon (BC) during any time of day at Varanasi and 4% at Ranchi. This study also estimated the loss of wheat crop at Varanasi and Ranchi while using the empirical model that was developed by Ahmed and Hassen [32] as −149 kg/ha and −141 kg/ha, respectively, due to the reduction of solar radiation because of atmospheric black carbon.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A statistical model of historical rice harvest in India, coupled with a regional climate scenario, indicated that there has been a slowdown in the increase in production over the last two decades due to increased brown cloud and greenhouse gas [30]. Similarly, Latha et al [31] compared the radiative forcing of atmospheric black carbon at two locations in IGP, Varanasi and Ranchi by using Santa Barbara DISTORT Atmospheric Radiative Transfer (SBDART) model and concluded that the incoming radiation is reduced by about 5% due to black carbon (BC) during any time of day at Varanasi and 4% at Ranchi. This study also estimated the loss of wheat crop at Varanasi and Ranchi while using the empirical model that was developed by Ahmed and Hassen [32] as −149 kg/ha and −141 kg/ha, respectively, due to the reduction of solar radiation because of atmospheric black carbon.…”
Section: Introductionmentioning
confidence: 97%
“…Das et al [37] studied winter haze in the eastern Indo Gangetic Basin through ground measurements during December 2013 to February 2014 and the radiative effect of haze by using SBDART and found the radiative forcing at the BOA in Silguri, Kolkata and Sunderban was −39.3, −70.3 and −38 Wm −2 respectively. In addition, Latha et al [31] studied the radiative forcing of atmospheric black carbon at Varanasi and Ranchi using SBDART and concluded that the radiative forcing due to atmospheric black carbon is significantly increased from February to March (i.e., from −30 Wm −2 to −50 Wm −2 ) at Varanasi due to an increased BC concentration and mixing layer height. The radiative forcing due to atmospheric aerosols at IGP stations has been studied at the annual, seasonal, and in some cases, monthly time scale by using radiative transfer models [36,[38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…The winter season is characterized by a shallower boundary layer, lower wind speed and low precipitation, leading to the accumulation of aerosols near the surface 2,14,15 . Along with the obvious health impacts, studies have shown that the high aerosol loading in winter can reduce radiation reaching to the surface by about 25%, thereby decreasing crop yield 1618 . Nonetheless, aerosols act as cloud condensation nuclei and affect cloud formation and rainfall 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Wind from the west and northwest prevails over this region in November. In November, crop burning and harvesting are common practices in Punjab and Haryana; these practices exert a substantial effect on the study site . The calm and stable atmospheric conditions as well as the low boundary layer contribute to an increasing concentration of pollutants.…”
Section: Resultsmentioning
confidence: 99%
“…Agra supports the transport of dust from the long range over the north Indian region in November, leading to higher concentrations of PM 10 practices exert a substantial effect on the study site. [23,58] The calm and stable atmospheric conditions as well as the low boundary layer contribute to an increasing concentration of pollutants. These conditions retain the high loading of PM 10 and PM 2.5 in the ambient air for a long period.…”
Section: Role Of Meteorological Parameters and Long-range Transportmentioning
confidence: 99%